PENERAPAN HUKUM TERHADAP TINDAK PIDANA SUAP TERKAIT KEBIJAKAN PENGHAPUSAN BENSIN BERTIMBAL DI INDONESIA - -, Pujiyarto (MEDIA HUKUM, 2014)
The criminal bribes that shortly needed to wipe out in Indonesia is a bribe case. In one of bribe cases that are very interesting is a bribe case that being done by the Innospect Ltd Company in England to the some officers at the Office of Energy and Mineral Resources Department of Republic Indonesia that has involved the General Director of Energy and Mineral Resources. The juridical point that is needed to be learnt in this case is about the General Director status who has involved in corruption case, especially to analysis the formulation of the criminal corruptions in the criminal law systems in Indonesia and the applying the legal regulations of criminal law especially on the criminal bribes in the case of eradicating the fake gasoline in Indonesia.